Vegetation analysis of the upstream Cianjur watershets in Mount Gede-Pangrango National Park’s - ARRIJANI ARRIJANI; DEDE SETIADI; EDI GUHARDJA; IBNUL QAYIM (Society for Indonesian Biodiversity, 2006)
The objective of this study was to found the composition and structure of vegetation at the upstream Cianjur Watersheds. Research sampling conducted by using plot method placed purposive random sampling at research location with increase elevation equal to 100 m from sea level. Every 100 m elevation level, were taken 5 sample plots so that up to 1000-1500 (sub-montana zone) totalize plot were 30. Measured parameter cover density, frequency, dominancy, Important Value Index (IVI), Diversity Index (H'), and Evenness (E). The subdividing pattern plot done through cluster analysis. The result of this research indicate that species puspa (Schima wallichii) and rasamala (Altingia excelsa) were two species with highest Important Value Indeks, so that both species considered to be dominant the community. The species diversity index (H’) equal to 3,38 categorized to high, but the evenness value (E) was categorized to low (1.95). The phenomena happened because tha distribution of species were heterogenous. The Cluster analysis indicated that there were three sub-groups which can be categorized as sub-zone in sub-montana zone, namely the sub-zone lower, middle and hight. © 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: vegetation analysis, Upstream Cianjur watersheds, Sub-montana zone, Mt.Gede-Pangrango National Park’s.